The Best You: Gym Based Machine Learning Application - MNN. Hasni; Sasfak Ahamed A.G; Shajith M.S.M; Ahamed M.B.B; Hansi De Silva (International Journal of Engineering and Management Research, 2022)
Use of artificial intelligence (AI) and machine learning is rapidly becoming more widespread in the 21st century. Both are quickly emerging increasingly vital aspects of today's standard exercise routines. Artificial intelligence has become inextricably linked to health and fitness. Experts in the field of technology believe that AI will solve all problems. When it comes to fitness, it has the ability to empower the app by drastically increasing engagement, which may lead to long-term income. In other words, it has the potential to make money. Apps that are equipped with AI have the potential to provide consumers a wide range of benefits. It is feasible for a person who is interested in fitness to save money because an artificial intelligence fitness trainer is more cost-effective than a human trainer. On the other hand, joining a gym may be cost prohibitive or just not doable given our hectic schedules. Aside from that, using fitness software that is powered by AI might make working out more fascinating and fun. In this section, we will discuss some of the best fitness applications that are powered by AI and machine learning models. This app creates unique training plans for each user using artificial intelligence This app was originally designed exclusively for use in gyms, but it recently changed its focus to meet the rising demand for at-home exercise. Simply put, FitnessAI pushes users to effectively build muscle every time they exercise by optimizing their weight lifting sets, repetitions, and weights for each activity. The main purpose of proposing this application system is to provide gym-goers with the right information at the right time, preventing them from taking the wrong supplements to maintain their body well.